Talking Stick Learning Model on Student Learning Outcomes in Subtheme 2 The Importance of Clean Air for Class V Respiration UPTD SDN 124385 Pematangsiantar - Etchy Wifana Eviralina Damanik (International Journal of Integrated Science and Technology, 2023)
The background to this research is based on activities carried out by researchers in class V UPTD SDN 124385 Pematang Siantar, namely the teacher still uses conventional learning models so that students are less active in the learning process. This causes the learning process to be less than optimal and student learning outcomes have not been achieved in accordance with the Minimum Completeness Criteria. From this problem, it is necessary to find a solution, namely by implementing the Talking Stick learning model . This learning model is suitable to be applied to thematic learning becausethis learning model invites students to be more active and can train students' mentality and courage in providing their own opinions. This learning model can improve the quality of thematic learning and also influence student learning outcomes. This type of research uses a pre-experimental method with a research design using a one group pretest-posttest design with a sample of 25 students. Based on the results of the data analysis tests carried out, thehypothesis test results obtained were tcount = 11.658 and ttable 2.064 with tcount > ttable = 11.658 > 2.064, so Ho was rejected and Ha was accepted. With thisexplanation, it can be concluded that there is an influence of the Talking Stick learning mode on student learning outcomes in subtheme 2 the importance of clean air for breathing in class V UPTD SDN 124385 Pematang Siantar.